2021
DOI: 10.3390/nu13072277
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Gene Expression Profiles of Rat Tissues after Mild and Short-Term Calorie Restrictions

Abstract: Many studies have shown the beneficial effects of calorie restriction (CR) on rodents’ aging; however, the molecular mechanism explaining these beneficial effects is still not fully understood. Previously, we conducted transcriptomic analysis on rat liver with short-term and mild-to-moderate CR to elucidate its early response to such diet. Here, we expanded transcriptome analysis to muscle, adipose tissue, intestine, and brain and compared the gene expression profiles of these multiple organs and of our previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Moreover, various CR regimens have been shown to affect some common molecular targets. We confirmed that in our model the hepatic gene expression of fasn , acly , and sirt1 followed typical patterns for CR [ 20 , 21 ]. Generally, although SCR exerts smaller metabolic effects than those expected of a long-term intervention, it is more feasible to carry out in humans [ 29 ], which was also a reason to choose it for the current study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, various CR regimens have been shown to affect some common molecular targets. We confirmed that in our model the hepatic gene expression of fasn , acly , and sirt1 followed typical patterns for CR [ 20 , 21 ]. Generally, although SCR exerts smaller metabolic effects than those expected of a long-term intervention, it is more feasible to carry out in humans [ 29 ], which was also a reason to choose it for the current study.…”
Section: Discussionsupporting
confidence: 83%
“…Various regimens of CR affect the expression of common target genes [ 20 , 21 ]. To examine whether SCR leads to similar changes, we analyzed the hepatic mRNA expression of fatty acid synthase ( fasn ) and ATP-citrate lyase ( acly ), i.e., genes encoding lipogenic enzymes downregulated by CR, as well as sirtuin 1 ( sirt1 ), encoding a deacetylase typically upregulated by CR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, short-term CR results in a striking degree of altered gene expression in the amygdala of mice who demonstrate an anxiolytic behavioural profile [ 15 ]. Gene expression changes in the hypothalamus, another key brain region involved in the regulation of anxiety [ 21 ], are also evident in mice [ 22 ] and rats [ 23 ] undergoing a short-term mild to moderate (5% to 30%) calorie reduced diet. Moreover, many of the identified genes altered as a consequence of CR are associated with the Hypothalamic-Pituitary-Adrenal (HPA) axis [ 15 , 22 , 24 ], also heavily implicated in the pathogenesis of anxiety disorders (see [ 25 ] for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the low protein diet group was given a standard feed modification with a 5% feed protein of the total energy a day [16]. The low protein-energy diet group used the 30 percent feed restriction from the control diet to make the rats undernourished [17]. The rats were acclimatized for a week prior to treatment to ensure consistent physical and psychological conditions.…”
Section: Methodsmentioning
confidence: 99%